Chronic effects of occupational exposure to mineral fibres and recurrent chest infections in insulators. Issue 2 (30th May 2022) - Moitra, Subhabrata; Farshchi Tabrizi, Ali; Henderson, Linda; Khadour, Fadi; Osman, Mohamed; Melenka, Lyle; Lacy, Paige
Mineral fibres, which are types of commercially produced man-made vitreous fibres (MMVFs) with a woolly consistency, are industrially manufactured by passing air through molten glass, rock or slag, and are commonly known as glass, slag or rock wool. Although all these materials are grouped together as mineral fibres, there are differences in their composition and physical properties. Glass wool/fibreglass is made from borosilicate glass, which is composed of sand, soda ash dolomite, limestone, ulexite and anhydrite, while rock and slag wools are produced from naturally occurring igneous rock (basalt or dolomite rocks) and molten furnace slag, respectively [1]. These disorganised, interlocking fibres were reported to deliver potentially deleterious health effects, particularly on the skin and upper respiratory tract, to workers occupationally exposed to these materials, such as during installation or removal of insulation [2, 3]. While a few studies reported no evidence of pneumoconiosis in the industrial workers exposed to glass, rock or slag wool [4], several case reports appeared in recent years describing a long biopersistence of MMVFs leading to the development of pulmonary fibrosis at a later stage [5–8]. However, evidence of mineral fibre-associated respiratory tract infections has been limited. In this study, we aimed to investigate whether occupational exposure to mineral fibres was associated with recurrent chest infections. Exposure to mineral fibres (man-made forms of vitreous fibres often used as insulating material) is a risk factor for recurrent chest infections among workers, underscoring the necessity of workplace surveillance for protection from hazardous substances https://bit.ly/38cUpmA